THE SOCIAL AND PEDAGOGICAL FUNCTION OF HIGHER EDUCATION INSTITUTIONS IN THE UPBRINGING OF THE MODERN SPECIALIST - Parmankulov Farkhad Nurali o'g'li (Bright Mind Publishing, 2025)
The article proposes the socio-pedagogical function of a technical university as an independent object of pedagogical research. The essence of this function is substantiated, and the dynamics of its transformation depending on socio-cultural conditions are identified. It is demonstrated that the development of the socio-pedagogical function is associated with changes in role positions, goal orientation, and the profile-industry direction of educational activities. A socio-pedagogical approach to the upbringing of a specialist in a higher education institution is justified, which defines a strategic process of continuous movement toward the desired outcome — the ideal image of a modern specialist. The model of the specialist is dynamically formed based on the demands and expectations of the subjects of socio-economic activity (the state, society, academic staff, students, and university graduates), who create the components of a dynamically evolving model (competencies, competences, and personal qualities).
Keywords: Competence, competencies, personal qualities, educational process, conceptual framework, constructive specialist, invariant factors.